Identification of a Novel Astrovirus in Pinnipeds - Zhang, Peijun; Su, Haoxiang; Peng, Ruoyan; Chan, Jasper Fuk-Woo; Bai, Shijie; Wang, Gaoyu; Huang, Yi; Hu, Xiaoyuan; Luo, Jun; Liu, Sisi; Li, Youyou; Xue, Liying; et al. (Frontiers in Microbiology, 2022)
Astroviruses infect human and animals, causing diarrhea, fever, vomiting, and in severe cases, infant death. Previous evidence has shown that the cross-species transmission of avastroviral infections may be frequent among humans, mammals, and poultry. Mamastrovirus 11, a species of Mamastrovirus, was first reported in 2018 in California sea lion fecal samples in the United States, and the genome sequence of capsid protein was submitted to the Genebank, while the gene sequence of the non-structural protein region was still unclear. In this study, two novel astrovirus genome sequences, AstroV-HMU-1 and AstroV-like-HMU-2 were obtained from California sea lions (Zalophus californianus) and walruses (Odobenus rosmarus) host with the symptoms of chronic diarrhea, respectively. In phylogenetic analysis, the capsid protein (CP) of AstroV-HMU-1 closely clustered with Mamastrovirus 11, and the RNA-dependent RNA polymerase (RdRp) or serine protease (SP) of AstroV-HMU-1 were closely related to Mink astroviruse in the genus Mamastrovirus. The genome of AstroV-HMU-1 provided basic genomic information on NS protein regions of Mamastrovirus 11. Recombination analyses suggested that the genomes of Zalophus californianus AstroV-HMU-1, VA2/human, and mink astrovirus had likely recombined in distant times. The NS of AstroV-like-HMU-2 was separated from the Astroviridae family in the deep root of the phylogenetic tree and exhibited 36% amino acid identity with other mamastroviruse. It was proposed as member of a new genus in the unclassified Astroviridae. The results suggest a link between the novel astrovirus infection and chronic diarrhea of pinnipeds host. The novel marine mammalian astrovirus provides a scientific basis for animal-borne infectious diseases.